Abundance analysis of three metal poor stars: CS 22166-0030, CS 22186-0005, and CS 30344-0033. Issue Volume 9:Issue S298(2013) (6th January 2014) - Çalışkan, Şeyma; Caffau, Elisabetta; Bonifacio, Piercarlo; Sbordone, Luca; Albayrak, Berahitdin
Abstract: We present the abundance analysis of three very metal poor stars, CS 22166-0030 ([Fe/H]=−2.96), CS 22186-0005 ([Fe/H]=−2.70), and CS 30344-0033 ([Fe/H]=−2.90). Our study is based on high resolution spectra which were obtained from SARG (on TNG), HARPS (on 3.6m), and UVES (on VLT) spectrographs and one-dimensional ATLAS9 model atmospheres. We derived the abundances for 2, 9, and 16 atomic species in the spectrum of CS 22166-0030, CS 22186-0005, and CS 30344-0033, respectively. The Na and Mg abundances of CS 22166-0030 are highly under-abundant with respect to the solar values. The abundance patterns of CS 22186-0005 and CS 30344-0033 are consistent with the other halo stars within abundance uncertainties.